Road Speed Profile at Accident Prone-Areas in Universiti Teknologi PETRONAS (UTP) - Mohd Sharif, Noor Shaerra Amiera (IRC, 2016)
Speed can be defined as a measure of two different transportation performance characteristics, mobility and safety. From the previous research, they stated that the probability of a vehicle meet with an accident is greater when the vehicle speed deviation is higher form the average speed. In UTP, road accident statistic shows that the number of accident is increasing. Thus, this research is conducted to analyze the speed profile in Universiti Teknologi PETRONAS (UTP).